2021
DOI: 10.3390/pharmaceutics13122047
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Statins: New Therapeutic Approaches to Chronic, Recurrent Infection by Staphylococcus aureus

Abstract: An emergent approach to bacterial infection is the use of host rather than bacterial-directed strategies. This approach has the potential to improve efficacy in especially challenging infection settings, including chronic, recurrent infection due to intracellular pathogens. For nearly two decades, the pleiotropic effects of statin drugs have been examined for therapeutic usefulness beyond the treatment of hypercholesterolemia. Interest originated after retrospective studies reported decreases in the risk of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Subsequent studies have reported similar findings, signifying that prior use of statins reduced the disease progression and mortality of pneumonia and sepsis in clinical cases. Other evidence has also corroborated that patients prescribed statins for cholesterol-lowering exhibit a significantly decreased risk of contracting bacterial infections and improved survival during infections [59]. Therefore, it is widely acknowledged that a strong possibility exists for repurposing statins as future antimicrobial and antibiofilm therapeutics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Subsequent studies have reported similar findings, signifying that prior use of statins reduced the disease progression and mortality of pneumonia and sepsis in clinical cases. Other evidence has also corroborated that patients prescribed statins for cholesterol-lowering exhibit a significantly decreased risk of contracting bacterial infections and improved survival during infections [59]. Therefore, it is widely acknowledged that a strong possibility exists for repurposing statins as future antimicrobial and antibiofilm therapeutics.…”
Section: Discussionmentioning
confidence: 98%
“…Other reports have suggested that the antimicrobial effects of statins might be primarily because of the pleiotropic activities, e.g., statin mediated inhibition of hydrophobic isoprenoid intermediates viz., farnesyl pyrophosphate (Fpp) and geranylgeranyl pyrophosphate (GGpp). The decreased synthesis of these hydrophobic isoprenoid intermediates might be responsible for the pleiotropic effects of statin [59]. Many other studies have also substantiated that the underlying mechanism for antimicrobial efficacy of statin largely relies on the pleiotropic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies do not have a direct clinical impact to prevent or treat S. aureus infections, they pave the way to a new non-antibiotic approach to S. aureus infection treatment, by highlighting new host cell therapeutic targets. Indeed, because of S. aureus high propension to become resistant to current antimicrobial strategies, it would be relevant to directly focus on host cell targets instead of the bacterium (Evans and McDowell, 2021). Also, by exploring drug repurposing, time and money could be saved by using already available molecules that can act on newly discovered therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…This could be an easy-to-implement, faster and safer alternative to new antimicrobial development in the threatening context of S. aureus antibiotic multiresistance (Tacconelli et al, 2018). This approach has already been reviewed by Evans and McDowell, where statins were used as prophylactic agents and adjuvant therapy against intracellular S. aureus in different clinical studies (Evans and McDowell, 2021). Statins have shown to reduce the risk of contracting S. aureus infections and improve survival rate to infections by disturbing the integrity of the host cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of GGPP and the mevalonate pathway in peptidoglycan synthesis has led to the investigation of statins as potential antimicrobial agents. By inhibiting HMG-CoA reductase and blocking the production of mevalonate, statins can decrease the availability of isoprenoid intermediates and inhibit peptidoglycan synthesis, ultimately leading to bacterial growth inhibition or death [ 63 ]. Some studies suggest that statins can also modulate the expression of genes involved in beta-lactam resistance, further enhancing their antimicrobial efficacy against resistant bacteria [ 64 ].…”
Section: Antibacterial Effects Of Statinsmentioning
confidence: 99%